Diffuse Systemic Sclerosis with Interstitial Lung Disease and Severe Pulmonary Arterial Hypertension: A Case Report - Inamdar, Syed Zia; Londhe, Sushilkumar; Mehta, Ravina; Katageri, Sumanyu; Biradar, Siddanagouda; Devaramani, Shashidhar; Badiger, Sharan (Journal of Pharmacy Practice and Community Medicine)
Systemic sclerosis is a rare connective tissue disease categorized by extensive lung fibrosis, vascular and immunologic abnormalities. Autoimmune antibodies like anticentromere, anti-Scl-70 (anti-topoisomerase I), and anti-RNA polymerase II are commonly involved in progressive disease. Clinical presentations consist of Raynaud’s phenomenon, digital ulcers; pericardial effusion, and telangiectasia and are mostly associated with pulmonary complications like interstitial lung disease and pulmonary arterial hypertension. Disease-specific therapy is unavailable instead; symptomatic management is only the line of treatment. We report here a case of diffuse systemic sclerosis with interstitial lung disease and pulmonary arterial hypertension.
Keywords: Diffuse systemic sclerosis; Interstitial lung disease; Pulmonary arterial hypertension; Raynaud’s phenomenon